A ptf e hollow fiber membrane for treating heavy metal ions and a method for manufacturing the same
Patent Information
- Application Number
- CN202610456221.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-08
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-04-08
AI Technical Summary
Existing PTFE hollow fiber membranes face challenges in heavy metal ion treatment, including difficulties in functionalization due to surface inertness, an imbalance between adsorption capacity and selectivity of modification methods, and easy degradation of membrane structure under extreme environments.
A PDA coating is formed by the self-polymerization of dopamine hydrochloride, which is loaded with nano-iron oxide and filled with 1-butyl-3-methylimidazolium hexafluorophosphate using a vacuum-pressure impregnation method to construct a surface-pore synergistic structure, thereby achieving multi-stage treatment of physical interception, chemical adsorption and ion exchange.
It significantly improves the efficiency and stability of heavy metal ion treatment, especially maintaining structural integrity in strong acid and alkaline environments, and possesses high selective adsorption capacity and long-term stability.
Abstract
Description
Technical Field
[0001] This application relates to the field of hollow fiber membrane materials technology, and mainly to a PTFE hollow fiber membrane for treating heavy metal ions and its preparation method. Background Technology
[0002] Hollow fiber membranes are polymeric separation materials with a hollow tubular structure. Their porous structure endows them with a high specific surface area and excellent material separation performance. PTFE (polytetrafluoroethylene) hollow fiber membranes, due to the chemical inertness resulting from the dense arrangement of fluorine atoms, good mechanical strength, and high-temperature resistance, show broad application potential in fields such as heavy metal wastewater treatment, seawater desalination, and biopharmaceutical separation. The microporous structure of this type of membrane allows for precise retention of ions, colloids, and macromolecules; however, its surface chemical inertness limits the depth of functionalization modification.
[0003] Existing PTFE hollow fiber membranes face three major challenges in the treatment of heavy metal ions: First, surface inertness makes functional modification difficult, making it hard to construct an efficient adsorption layer; second, single modification methods result in an imbalance between adsorption capacity and selectivity; and third, under extreme environments such as strong acids and alkalis, the membrane structure is prone to performance degradation due to chemical corrosion or physical stress, manifested as decreased adsorption capacity, coating peeling, or pore blockage, which seriously affects treatment efficiency and long-term stability.
[0004] Therefore, existing technologies still need to be improved and developed. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this application is to provide a PTFE hollow fiber membrane for treating heavy metal ions and a method for preparing the same.
[0006] The technical solution of this application is as follows: A method for preparing a PTFE hollow fiber membrane for treating heavy metal ions includes the following steps: A dopamine hydrochloride solution was prepared using water, dopamine hydrochloride, and tris(hydroxymethyl)aminomethane. The pH value of the dopamine hydrochloride solution was 8.5 ± 0.2. A nano-iron oxide suspension was prepared by ultrasonic mixing of water, nano-iron oxide, and sodium dodecyl sulfate. The PTFE hollow fiber membrane to be treated is immersed in dopamine hydrochloride solution and reacted for 12-24 hours to obtain the primary modified PTFE hollow fiber membrane. The primary modified PTFE hollow fiber membrane was immersed in a nano iron oxide suspension and ultrasonically treated to obtain the secondary modified PTFE hollow fiber membrane. A secondary modified PTFE hollow fiber membrane was immersed in 1-butyl-3-methylimidazolium hexafluorophosphate using a vacuum-pressure impregnation method to obtain a tertiary modified PTFE hollow fiber membrane. The PTFE hollow fiber membrane, modified three times, is dried to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
[0007] Furthermore, when the modified PTFE hollow fiber membrane is first immersed in the nano iron oxide suspension, the ultrasonic treatment conditions are: 20-60 minutes, ultrasonic power of 50-150W, and frequency of 35-45kHz.
[0008] Furthermore, the vacuum-pressure impregnation method includes: The modified PTFE hollow fiber membrane was immersed in 1-butyl-3-methylimidazolium hexafluorophosphate, and the air pressure in the immersion container was reduced to near vacuum for 20-60 minutes. After vacuum treatment, inert gas is introduced and the pressure is gradually increased to 0.5MPa±0.05, and maintained for 1-2 hours to allow the ionic liquid to fill the membrane pores, thus obtaining a tertiary modified PTFE hollow fiber membrane.
[0009] Furthermore, the preparation of the nano iron oxide suspension includes: adding nano iron oxide and sodium dodecyl sulfate to water, stirring at 250-350 rpm for 5-20 minutes to obtain a mixed solution; The mixed solution was dispersed for 20-60 minutes under ultrasonic power of 100-300W and frequency of 35-45kHz to obtain a nano iron oxide suspension.
[0010] Furthermore, drying the tertiary modified PTFE hollow fiber membrane includes: desiccating the tertiary modified PTFE hollow fiber membrane; Then, it is vacuum dried at 35-45℃ for 24-48 hours with a vacuum degree of 0.08MPa±0.005 to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
[0011] Furthermore, the PTFE hollow fiber membrane to be treated is pretreated and then immersed in a dopamine hydrochloride solution; The pretreatment of the PTFE hollow fiber membrane to be treated includes: The PTFE hollow fiber membrane to be treated was ultrasonically cleaned using an ethanol solution. Take out the PTFE hollow fiber membrane to be treated, rinse it with water until the pH value of the effluent is 6.5-7.5, and then vacuum dry it at 35-45℃ for 12-24 hours with a vacuum degree of 0.08±0.02MPa to obtain the pretreated PTFE hollow fiber membrane.
[0012] Furthermore, ultrasonic cleaning of the PTFE hollow fiber membrane to be treated using ethanol solution includes: immersing the PTFE hollow fiber membrane to be treated in ethanol solution and ultrasonically cleaning for 20-60 minutes under ultrasonic power of 100-300W and frequency of 35-45kHz.
[0013] Furthermore, the preparation of the PTFE hollow fiber membrane to be treated includes: PTFE resin and additive oil are mixed, and then preformed and extruded to obtain nascent PTFE hollow fibers. Nascent PTFE hollow fibers were heat-treated at a temperature of 300℃-350℃ for 60min-150min to obtain heat-treated PTFE hollow fibers. Heat-treated PTFE hollow fibers were stretched under the conditions of stretching temperature 30℃-330℃, stretching ratio 0.5-10 times, and stretching speed 0.3m / min-35m / min to obtain stretched PTFE hollow fibers. PTFE hollow fibers were sintered and stretched under the conditions of sintering and shaping temperature of 330℃-370℃ and sintering time of 5min-20min. Stretched PTFE hollow fibers are cooled to obtain a PTFE hollow fiber membrane to be processed.
[0014] This application also provides a PTFE hollow fiber membrane for treating heavy metal ions.
[0015] Furthermore, the PTFE hollow fiber membrane to be treated comprises 95-105 parts by weight, dopamine hydrochloride comprises 0.1-1 parts by weight, tris(hydroxymethyl)aminomethane comprises 0.1-1 parts by weight, nano-iron oxide comprises 0.1-1 parts by weight, sodium dodecyl sulfate comprises 0.01-0.1 parts by weight, 1-butyl-3-methylimidazolium hexafluorophosphate comprises 38-48 parts by weight, and water comprises 800-1500 parts by weight.
[0016] In the preparation method of this application, a PDA coating is first formed by the self-polymerization of dopamine hydrochloride on the membrane surface, followed by the loading of nano-iron oxide and then the filling of ionic liquid (1-butyl-3-methylimidazolium hexafluorophosphate). Under a specific preparation sequence, a high-performance PTFE hollow fiber membrane for treating heavy metal ions is obtained.
[0017] Specifically, a PDA coating is formed on the surface of the PTFE hollow fiber membrane through the self-polymerization of dopamine hydrochloride. This coating, through catechol / amino groups, exhibits strong adhesion and chemical bonding with the membrane surface, constructing an active interface. This provides directional anchors for the subsequent loading of nano-iron oxide—the polar groups of the PDA coating can actively capture iron oxide particles through coordination bonds, hydrogen bonds, or electrostatic interactions, ensuring that the loading process transforms from random attachment to precise bonding, laying the structural foundation for the formation of subsequent functional layers.
[0018] Nano-iron oxide was loaded onto a primary modified PTFE hollow fiber membrane, and the adhesive properties of PDA were utilized to achieve uniform distribution and stable fixation of the nano-iron oxide particles. The PDA coating not only served as a physical carrier for the iron oxide but also promoted the initial adsorption reaction between the nano-iron oxide and heavy metal ions through its chemical activity. The high specific surface area of the nano-iron oxide combined with the biocompatibility of PDA formed a dual mechanism of chemical adsorption and physical interception, enabling the membrane surface to initially possess the ability to capture heavy metals.
[0019] 1-Butyl-3-methylimidazolium hexafluorophosphate is filled into the membrane pores using a vacuum-pressure impregnation method. This step, together with the previous two steps, forms a three-dimensional synergy between the surface and the pores. Within the pores, 1-Butyl-3-methylimidazolium hexafluorophosphate forms an ion exchange layer, which, together with the PDA-nano iron oxide composite structure on the surface, constructs a three-stage treatment system of surface adsorption + pore trapping + ion exchange. The PDA-nano iron oxide composite structure on the surface of the PTFE hollow fiber membrane, used for treating heavy metal ions, captures heavy metals through chemisorption, while the 1-Butyl-3-methylimidazolium hexafluorophosphate within the pores further enhances the fixation and separation of heavy metals through ion exchange. This surface-to-inside filling sequence ensures that 1-Butyl-3-methylimidazolium hexafluorophosphate neither damages the surface functional layer nor fails to deeply fill the pores, ultimately forming a synergistic structure of outer layer adsorption and inner layer exchange.
[0020] In other words, the PDA coating provides a stable loading platform for nano-iron oxide, while the nano-iron oxide loading creates an "active surface + porous space" for the 1-butyl-3-methylimidazolium hexafluorophosphate filling. The 1-butyl-3-methylimidazolium hexafluorophosphate filling then forms an "inner-outer" synergy with the PDA-nano-iron oxide composite structure on the surface through pore penetration. The specific preparation sequence provided in this application avoids mutual interference between functional layers, enabling the final PTFE hollow fiber membrane for treating heavy metal ions to combine the adhesiveness of PDA, the adsorption activity of nano-iron oxide, and the ion exchange capacity of 1-butyl-3-methylimidazolium hexafluorophosphate. This forms a multi-level synergistic treatment of heavy metal ions through physical interception, chemical adsorption, and ion exchange, significantly improving the membrane's treatment efficiency and stability.
[0021] Meanwhile, the PTFE hollow fiber membrane used for treating heavy metal ions maintains high chemical stability even under strong acid and alkali environments. The pretreatment steps, including ultrasonic cleaning with ethanol, rinsing with deionized water, and vacuum drying, remove impurities from the membrane surface and reduce surface energy, providing a clean and low-tension substrate environment for subsequent modification, laying a synergistic foundation. The PDA coating self-polymerizes under weakly alkaline conditions to form an active interface. Its catechol / amino groups form chemical bonds with the membrane surface, acting as both directional anchors for nano-iron oxide and isolating direct contact between acids / alkalis and the substrate through a three-dimensional network structure, achieving a dual synergy of interface protection and functional bridging. The nano-iron oxide loading utilizes the adhesion of the PDA coating to achieve uniform distribution. Its high specific surface area and chemical activity, combined with the PDA coating, form a functional layer that enhances adsorption capacity and corrosion resistance. 1-Butyl-3-methylimidazolium hexafluorophosphate filling deeply penetrates the membrane pores through a vacuum-pressure impregnation method, forming an ion exchange layer. This layer, together with the surface composite structure, creates a three-dimensional synergy, strengthening the fixation of heavy metal ions and reducing acid and alkali erosion of the pores. Each step forms an interconnected synergistic chain, ultimately enabling the membrane to maintain its structural integrity in strong acid and alkaline environments, achieving efficient and stable heavy metal ion treatment capabilities, and fully demonstrating the synergistic advantages of multi-step synergy.
[0022] Compared with the prior art, this application has the following beneficial effects: 1. This application constructs an active interface through a PDA coating, providing directional anchors for nano-iron oxide and achieving precise loading. The high specific surface area and chemical activity of the nano-iron oxide form a dual mechanism of chemical adsorption and physical interception. 1-Butyl-3-methylimidazolium hexafluorophosphate fills the pores to form an ion exchange layer, constructing a three-stage treatment system of surface adsorption + pore retention + ion exchange with the surface composite structure. The three steps synergistically achieve multi-stage treatment of physical interception, chemical adsorption, and ion exchange, significantly improving the treatment effect of heavy metal ions.
[0023] 2. The synergistic effect of the catechol / amino groups of the PDA coating and the active sites of nano-iron oxide results in high selective adsorption of specific heavy metal ions Pb²⁺ and Cd²⁺. This selectivity stems from the coordination between the polar groups of PDA and the heavy metal ions, as well as the exclusive adsorption sites provided by the high specific surface area of nano-iron oxide, ensuring precise capture of target heavy metals in complex systems with strong anti-interference capabilities.
[0024] 3. The unique structure of the PTFE hollow fiber membrane used for treating heavy metal ions effectively isolates acids and alkalis from direct contact with the substrate, and chemical bonding enhances interface protection. The corrosion resistance of nano-iron oxide is synergistically strengthened by PDA, and 1-butyl-3-methylimidazolium hexafluorophosphate fills the pores to form an ion exchange layer, reducing acid and alkali erosion of the pores. The PTFE hollow fiber membrane used for treating heavy metal ions maintains structural integrity in strong acid and alkali environments, exhibiting excellent long-term stability. Detailed Implementation
[0025] To facilitate understanding of this application, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of this application.
[0026] This application provides a PTFE hollow fiber membrane for treating heavy metal ions, comprising the following raw materials: PTFE hollow fiber membrane to be treated: 95-105 parts by weight, commercially available or homemade; Dopamine hydrochloride: 0.1-1 parts by weight, commercially available; Tris(hydroxymethyl)aminomethane: 0.1-1 parts by weight, commercially available; Nano iron oxide: 0.1-1 parts by weight, commercially available; Sodium dodecyl sulfate: 0.01-0.1 parts by weight, commercially available; 1-Butyl-3-methylimidazolium hexafluorophosphate: 38-48 parts by weight, commercially available; Water: 800-1500 parts by weight.
[0027] If the PTFE hollow fiber membrane to be treated is self-made, the following preparation method shall be used: Step a: Preparation of nascent PTFE hollow fibers: Mix commercially available PTFE resin (molecular weight of 2-4 million, compression ratio of 400-600 times, crystallinity greater than 98%) with auxiliary oil (preferably naphtha).
[0028] After the two are mixed evenly, they are pre-formed into compacts using a hydraulic device. Then, nascent PTFE hollow fibers are produced by a push-forming equipment, with an outer diameter of 0.8mm-5.0mm and a wall thickness of 0.2mm-1.2mm.
[0029] Step b: Heat treatment: Nascent PTFE hollow fibers are heat-treated at a temperature of 300℃-350℃ for 60min-150min to obtain heat-treated PTFE hollow fibers.
[0030] Step c: Stretch to create a hole: Heat-treated PTFE hollow fibers were stretched under the conditions of stretching temperature of 30℃-330℃, stretching ratio of 0.5-10 times, and stretching speed of 0.3m / min-35m / min to obtain stretched PTFE hollow fibers.
[0031] Step d: Sintering and shaping: PTFE hollow fibers were sintered and stretched under sintering conditions of 330℃-370℃ and sintering time of 5min-20min.
[0032] After natural cooling, the PTFE hollow fiber membrane to be treated can be obtained.
[0033] This application also provides a method for preparing a PTFE hollow fiber membrane for treating heavy metal ions, comprising the following steps: Step 1. Pretreatment of the PTFE hollow fiber membrane to be treated: Immerse the PTFE hollow fiber membrane to be treated in an ethanol solution and place it in an ultrasonic cleaner for 20-60 minutes. The ultrasonic power is 100-300W and the frequency is 35-45kHz.
[0034] Remove the PTFE hollow fiber membrane to be treated and rinse it with plenty of deionized water until the pH of the effluent is 6.5-7.5 to remove the ethanol remaining on the membrane surface.
[0035] The cleaned PTFE hollow fiber membrane to be treated is placed in a vacuum drying oven and vacuum dried at 35-45℃ for 12-24 hours with a vacuum degree of 0.08±0.02MPa to obtain a pretreated PTFE hollow fiber membrane for later use.
[0036] Step 2. Preparation of dopamine hydrochloride solution: Add 400-600mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at a speed of 250-350rpm.
[0037] Add dopamine hydrochloride and tris(hydroxymethyl)aminomethane in sequence, and continue stirring until completely dissolved to obtain a dopamine hydrochloride solution.
[0038] Measure the pH of the dopamine hydrochloride solution using a pH meter, ensuring the pH is within 8.5 ± 0.2. If the pH deviates from the target value, adjust it to the target pH using hydrochloric acid or sodium hydroxide solution.
[0039] Step 3. Preparation of nano-iron oxide suspension: Add 400-600mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at a speed of 250-350rpm.
[0040] Add nano-iron oxide and sodium dodecyl sulfate, and continue stirring for 5-20 minutes to fully dissolve the sodium dodecyl sulfate, thus obtaining a mixed solution.
[0041] The mixed solution was placed in an ultrasonic cleaner and ultrasonically dispersed for 20-60 minutes at an ultrasonic power of 100-300W and a frequency of 35-45kHz to prepare a nano iron oxide suspension.
[0042] During ultrasonic dispersion, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0043] Step 4. Preparation of PDA coating: The pretreated PTFE hollow fiber membrane is immersed in a dopamine hydrochloride solution and left to stand at room temperature for 12-24 hours to allow the dopamine hydrochloride to self-polymerize on the membrane surface to form a PDA coating, thus obtaining the primary modified PTFE hollow fiber membrane.
[0044] During the soaking process, cover the mouth of the beaker with plastic wrap to reduce the oxidation of dopamine hydrochloride.
[0045] Step 5. Loading of nano-iron oxide: Remove the initially modified PTFE hollow fiber membrane and rinse it with deionized water to remove unreacted dopamine hydrochloride.
[0046] The rinsed primary modified PTFE hollow fiber membrane is immersed in a nano iron oxide suspension and placed in an ultrasonic cleaner for ultrasonic treatment for 20-60 minutes at an ultrasonic power of 50-150W and a frequency of 35-45kHz, so that the nano iron oxide is loaded onto the PDA coating to obtain a secondary modified PTFE hollow fiber membrane.
[0047] During the ultrasonic treatment, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0048] Step 6. Ionic liquid filling: Remove the secondary modified PTFE hollow fiber membrane and rinse it with deionized water to remove unloaded nano-iron oxide.
[0049] The secondary modified PTFE hollow fiber membrane was immersed in 38-48g of 1-butyl-3-methylimidazolium hexafluorophosphate using a vacuum-pressure impregnation method. The vacuum pump was started to reduce the pressure in the impregnation container to near vacuum (-0.1MPa±0.05) for 20-60 minutes.
[0050] After the vacuum treatment is completed, the vacuum pump is turned off, and an inert gas (such as nitrogen) is introduced into the container. The pressure is gradually increased to 0.5MPa±0.05 and maintained for 1-2 hours to allow the ionic liquid to fill the membrane pores, thus obtaining a tertiary modified PTFE hollow fiber membrane.
[0051] First, vacuum treatment (vacuuming): Objective: To remove air (gas) from the membrane pores, creating a negative pressure environment to provide impetus for subsequent liquid permeation.
[0052] Principle: Under negative pressure, the air inside the channel is extracted due to the pressure difference, forming a "cavity" inside the channel, creating space for the ionic liquid to enter.
[0053] Post-pressurization treatment: Objective: To use external pressure to "force" the ionic liquid into the vacuumed pores, ensuring complete filling.
[0054] Principle: Under positive pressure, the ionic liquid is "pushed" into the pore cavity due to the pressure difference, achieving deep penetration and filling.
[0055] Step 7. Drying: Remove the tertiary modified PTFE hollow fiber membrane and blot the surface of the ionic liquid with filter paper.
[0056] The tertiary modified PTFE hollow fiber membrane was placed in a vacuum drying oven and vacuum dried at 35-45℃ for 24-48 hours with a vacuum degree of 0.08MPa±0.005 to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
[0057] If Fe3O4 is loaded first and then PDA is self-polymerized, the PTFE membrane surface is highly hydrophobic. Direct loading of Fe3O4 (without PDA anchors) easily leads to particle aggregation and detachment (due to the lack of chemical bonding, relying solely on physical adsorption), reducing the density of adsorption sites and long-term stability. The post-polymerized PDA may encapsulate the already loaded Fe3O4 particles, blocking their surface active sites (such as hydroxyl groups and iron ions), resulting in poor treatment of heavy metal ions.
[0058] If 1-butyl-3-methylimidazolium hexafluorophosphate is filled first before subsequent steps, the ionic liquid may alter the solution pH or compete with dopamine hydrochloride for adsorption, inhibiting the self-polymerization rate of PDA and the uniformity of the coating. Within the pores filled with ionic liquid, Fe3O4 may only be loaded on the membrane surface or in the shallow pores, failing to penetrate deep into the pores, resulting in uneven distribution of adsorption sites and reduced deep adsorption capacity for heavy metal ions. The PDA coating may swell or undergo structural damage due to the presence of the ionic liquid, affecting the coating's mechanical strength and stability.
[0059] If PDA is self-polymerized first, then ionic liquid is filled, and then Fe3O4 is loaded, the ionic liquid may occupy the pore space after filling, causing Fe3O4 to be only loaded on the membrane surface and unable to enter the pores, thus reducing the space utilization of adsorption sites. During loading, Fe3O4 will also compete with the ionic liquid for adsorption, causing some Fe3O4 particles to be encapsulated by the ionic liquid, affecting their chemical bonding with the PDA coating and reducing loading stability.
[0060] The present application will be further described below through specific embodiments.
[0061] Example 1 The PTFE hollow fiber membrane to be treated is prepared using the following method: Step a: Preparation of nascent PTFE hollow fibers: Mix commercially available PTFE resin (molecular weight of 2 million, compression ratio of 400 times, crystallinity of 98%) with additive oil (naphtha).
[0062] After the two are mixed evenly, they are pre-formed into a compact using a hydraulic device. Then, nascent PTFE hollow fibers with an outer diameter of 2 mm and a wall thickness of 0.8 mm are obtained by a push-forming equipment.
[0063] Step b: Heat treatment: Nascent PTFE hollow fibers were heat-treated at a temperature of 300℃ for 120 minutes to obtain heat-treated PTFE hollow fibers.
[0064] Step c: Stretch to create a hole: Heat-treated PTFE hollow fibers were stretched at a stretching temperature of 100℃, a stretching ratio of 3 times, and a stretching rate of 0.5m / min to obtain stretched PTFE hollow fibers.
[0065] Step d: Sintering and shaping: PTFE hollow fibers were sintered and stretched under the conditions of sintering temperature of 350℃ and sintering time of 5min.
[0066] After natural cooling, the PTFE hollow fiber membrane to be treated can be obtained.
[0067] A method for preparing a PTFE hollow fiber membrane for treating heavy metal ions includes the following steps: Step 1. Pretreatment of the PTFE hollow fiber membrane to be treated: 100g of the PTFE hollow fiber membrane to be treated was immersed in 95% ethanol solution and placed in an ultrasonic cleaner for ultrasonic cleaning for 30 minutes at an ultrasonic power of 200W and a frequency of 40kHz.
[0068] Remove the PTFE hollow fiber membrane to be treated and rinse it with plenty of deionized water until the pH of the effluent is 7, in order to remove the ethanol remaining on the membrane surface.
[0069] The cleaned PTFE hollow fiber membrane to be treated was placed in a vacuum drying oven and vacuum dried at 40°C for 12 hours with a vacuum degree of 0.08 MPa to obtain a pretreated PTFE hollow fiber membrane for later use.
[0070] Step 2. Preparation of dopamine hydrochloride solution: Add 500 mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at 300 rpm.
[0071] Add 1g of dopamine hydrochloride and 0.4g of tris(hydroxymethyl)aminomethane in sequence, and continue stirring until completely dissolved to obtain a dopamine hydrochloride solution.
[0072] Measure the pH of the dopamine hydrochloride solution with a pH meter to ensure the pH is at 8.5. If the pH deviates from this value, adjust it to the target pH using hydrochloric acid or sodium hydroxide solution.
[0073] Step 3. Preparation of nano-iron oxide suspension: Add 500 mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at 300 rpm.
[0074] Add 0.3g of nano-iron oxide and 0.03g of sodium dodecyl sulfate, and continue stirring for 10 minutes to fully dissolve the sodium dodecyl sulfate, thus obtaining a mixed solution.
[0075] The mixed solution was placed in an ultrasonic cleaner and ultrasonically dispersed for 30 minutes at an ultrasonic power of 200W and a frequency of 40kHz to prepare a nano iron oxide suspension.
[0076] During ultrasonic dispersion, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0077] Step 4. Preparation of PDA coating: The pretreated PTFE hollow fiber membrane was immersed in a dopamine hydrochloride solution and left to stand at room temperature for 12 hours to allow the dopamine hydrochloride to self-polymerize on the membrane surface to form a PDA coating, thus obtaining the first modified PTFE hollow fiber membrane.
[0078] During the soaking process, cover the mouth of the beaker with plastic wrap to reduce the oxidation of dopamine hydrochloride.
[0079] Step 5. Loading of nano-iron oxide: Remove the initially modified PTFE hollow fiber membrane and rinse it with deionized water to remove unreacted dopamine hydrochloride.
[0080] The rinsed primary modified PTFE hollow fiber membrane was immersed in a nano iron oxide suspension and placed in an ultrasonic cleaner for 30 minutes of ultrasonic treatment at a power of 100W and a frequency of 40kHz, so that the nano iron oxide was loaded onto the PDA coating to obtain a secondary modified PTFE hollow fiber membrane.
[0081] During the ultrasonic treatment, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0082] Step 6. Ionic liquid filling: Remove the secondary modified PTFE hollow fiber membrane and rinse it with deionized water to remove unloaded nano-iron oxide.
[0083] The secondary modified PTFE hollow fiber membrane was immersed in 45g of 1-butyl-3-methylimidazolium hexafluorophosphate using a vacuum-pressure impregnation method. The vacuum pump was started to reduce the pressure in the impregnation container to near vacuum (-0.1MPa) for 30 minutes.
[0084] After the vacuum treatment is completed, the vacuum pump is turned off, and an inert gas (nitrogen) is introduced into the container. The pressure is gradually increased to 0.5 MPa and maintained for 1 hour to allow the ionic liquid to fill the membrane pores, thus obtaining a tertiary modified PTFE hollow fiber membrane.
[0085] Step 7. Drying: Remove the tertiary modified PTFE hollow fiber membrane and blot the surface of the ionic liquid with filter paper.
[0086] The tertiary modified PTFE hollow fiber membrane was placed in a vacuum drying oven and dried under vacuum at 40°C for 24 hours with a vacuum degree of 0.08 MPa to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
[0087] Performance testing: 1. Heavy metal ion adsorption performance testing: Static adsorption experiments were conducted by immersing 0.1 g of a PTFE hollow fiber membrane used for treating heavy metal ions into 100 mL of a solution containing 100 mg / L Pb. 2+ The solution was shaken at 25°C for 24 hours at a shaking speed of 150 rpm.
[0088] Then, the PTFE hollow fiber membrane used to treat heavy metal ions was removed, and the remaining Pb in the solution was measured. 2+ The concentration of heavy metals was determined to determine the amount of heavy metals adsorbed by the PTFE hollow fiber membrane used to treat heavy metal ions; then the adsorption capacity of the PTFE hollow fiber membrane used to treat heavy metal ions was calculated.
[0089] 2. Selective adsorption performance testing: Static adsorption experiments were conducted by immersing 0.1 g of a PTFE hollow fiber membrane used for treating heavy metal ions into 100 mL of a solution containing 100 mg / L Pb. 2+ and 100 mg / L Cd 2+ The mixed solution (using acetate-sodium acetate buffer to maintain pH at 5.5±0.2 to keep the system pH stable) was shaken at 25°C for 24 hours at a shaking speed of 150 rpm.
[0090] Then, the PTFE hollow fiber membrane used to treat heavy metal ions was removed, and the remaining Pb in the solution was measured. 2+ and Cd 2+The concentration of heavy metals was determined to determine the amount of heavy metals adsorbed by the PTFE hollow fiber membrane used to treat heavy metal ions; then the adsorption capacity of the PTFE hollow fiber membrane used to treat heavy metal ions was calculated.
[0091] 3. Flux: The PTFE hollow fiber membrane used to treat heavy metal ions is assembled into a membrane module. Pure water is used as feed water and the test is carried out at a pressure of 0.1 MPa. The volume of pure water passing through a unit area of membrane per unit time is recorded, and the pure water flux is calculated.
[0092] 4. Acid and alkali resistance: After flux testing, the PTFE hollow fiber membrane used for treating heavy metal ions was immersed in a sulfuric acid solution with a pH of 2 for 5 days, then removed, rinsed with water until the water pH reached 7, and dried. Next, the PTFE hollow fiber membrane used for treating heavy metal ions was immersed in a sodium hydroxide solution with a pH of 12 for 5 days, then removed, rinsed with water until the water pH reached 7, and dried. The pure water flux was then tested again.
[0093] Test results: 1. Heavy metal ion adsorption performance test: Pb 2+ The adsorption capacity is 55 mg / g.
[0094] 2. Selective adsorption performance testing: Pb 2+ The adsorption capacity was 51 mg / g, Cd 2+ The adsorption capacity is 6 mg / g.
[0095] 3. Flux: The pure water flux is 380 L / (m²). 2 ·h).
[0096] 4. Acid and alkali resistance: Pure water flux is 360L / (m³). 2 ·h).
[0097] Comparative Example 1 A method for preparing a PTFE hollow fiber membrane for treating heavy metal ions, which differs from Example 1 in that it includes the following steps: Step 1. Pretreatment of the PTFE hollow fiber membrane to be treated: 100g of the PTFE hollow fiber membrane to be treated was immersed in 95% ethanol solution and placed in an ultrasonic cleaner for ultrasonic cleaning for 30 minutes at an ultrasonic power of 200W and a frequency of 40kHz.
[0098] Remove the PTFE hollow fiber membrane to be treated and rinse it with plenty of deionized water until the pH of the effluent is 7, in order to remove the ethanol remaining on the membrane surface.
[0099] The cleaned PTFE hollow fiber membrane to be treated was placed in a vacuum drying oven and vacuum dried at 40°C for 12 hours with a vacuum degree of 0.08 MPa to obtain a pretreated PTFE hollow fiber membrane for later use.
[0100] Step 2. Preparation of dopamine hydrochloride solution: Add 500 mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at 300 rpm.
[0101] Add 1g of dopamine hydrochloride and 0.4g of tris(hydroxymethyl)aminomethane in sequence, and continue stirring until completely dissolved to obtain dopamine hydrochloride.
[0102] Measure the pH of the dopamine hydrochloride solution with a pH meter to ensure the pH is at 8.5. If the pH deviates from this value, adjust it to the target pH using hydrochloric acid or sodium hydroxide solution.
[0103] Step 3. Preparation of nano-iron oxide suspension: Add 500 mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at 300 rpm.
[0104] Add 0.3g of nano-iron oxide and 0.03g of sodium dodecyl sulfate, and continue stirring for 10 minutes to fully dissolve the sodium dodecyl sulfate, thus obtaining a mixed solution.
[0105] The mixed solution was placed in an ultrasonic cleaner and ultrasonically dispersed for 30 minutes at an ultrasonic power of 200W and a frequency of 40kHz to prepare a nano iron oxide suspension.
[0106] During ultrasonic dispersion, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0107] Step 4. Loading of nano-iron oxide: The pretreated PTFE hollow fiber membrane was immersed in a nano iron oxide suspension and placed in an ultrasonic cleaner for 30 minutes. The ultrasonic power was 100W and the frequency was 40kHz to load the nano iron oxide, thus obtaining the first modified PTFE hollow fiber membrane.
[0108] During the ultrasonic treatment, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0109] Step 5. Preparation of PDA coating: Remove the initially modified PTFE hollow fiber membrane and rinse it with deionized water to remove unloaded nano-iron oxide.
[0110] The primary modified PTFE hollow fiber membrane was immersed in a dopamine hydrochloride solution and left to stand at room temperature for 12 hours to allow the dopamine hydrochloride to self-polymerize on the membrane surface to form a PDA coating, thus obtaining a secondary modified PTFE hollow fiber membrane.
[0111] During the soaking process, cover the mouth of the beaker with plastic wrap to reduce the oxidation of dopamine hydrochloride.
[0112] Step 6. Ionic liquid filling: Remove the secondary modified PTFE hollow fiber membrane and rinse it with deionized water to remove unreacted dopamine hydrochloride.
[0113] The secondary modified PTFE hollow fiber membrane was immersed in 45g of 1-butyl-3-methylimidazolium hexafluorophosphate using a vacuum-pressure impregnation method. The vacuum pump was started to reduce the pressure in the impregnation container to near vacuum (-0.1MPa) for 30 minutes.
[0114] After the vacuum treatment is completed, the vacuum pump is turned off, and an inert gas (nitrogen) is introduced into the container. The pressure is gradually increased to 0.5 MPa and maintained for 1 hour to allow the ionic liquid to fill the container, thus obtaining a tertiary modified PTFE hollow fiber membrane.
[0115] Step 7. Drying: Remove the tertiary modified PTFE hollow fiber membrane and blot the surface of the ionic liquid with filter paper.
[0116] The tertiary modified PTFE hollow fiber membrane was placed in a vacuum drying oven and dried under vacuum at 40°C for 24 hours with a vacuum degree of 0.08 MPa to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
[0117] Test results: 1. Heavy metal ion adsorption performance test: Pb 2+ The adsorption capacity was 42 mg / g.
[0118] 2. Selective adsorption performance testing: Pb 2+ The adsorption capacity was 36 mg / g, Cd 2+ The adsorption capacity is 5 mg / g.
[0119] 3. Flux: The pure water flux is 330 L / (m²). 2 ·h).
[0120] 4. Acid and alkali resistance: Pure water flux is 280 L / (m³). 2 ·h).
[0121] Comparative Example 2 A method for preparing a PTFE hollow fiber membrane for treating heavy metal ions, which differs from Example 1 in that it includes the following steps: Step 1. Pretreatment of the PTFE hollow fiber membrane to be treated: 100g of the PTFE hollow fiber membrane to be treated was immersed in 95% ethanol solution and placed in an ultrasonic cleaner for ultrasonic cleaning for 30 minutes at an ultrasonic power of 200W and a frequency of 40kHz.
[0122] Remove the PTFE hollow fiber membrane to be treated and rinse it with plenty of deionized water until the pH of the effluent is 7, in order to remove the ethanol remaining on the membrane surface.
[0123] The cleaned PTFE hollow fiber membrane to be treated was placed in a vacuum drying oven and vacuum dried at 40°C for 12 hours with a vacuum degree of 0.08 MPa to obtain a pretreated PTFE hollow fiber membrane for later use.
[0124] Step 2. Preparation of dopamine hydrochloride solution: Add 500 mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at 300 rpm.
[0125] Add 1g of dopamine hydrochloride and 0.4g of tris(hydroxymethyl)aminomethane in sequence, and continue stirring until completely dissolved to obtain dopamine hydrochloride.
[0126] Measure the pH of the dopamine hydrochloride solution with a pH meter to ensure the pH is at 8.5. If the pH deviates from this value, adjust it to the target pH using hydrochloric acid or sodium hydroxide solution.
[0127] Step 3. Preparation of nano-iron oxide suspension: Add 500 mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at 300 rpm.
[0128] Add 0.3g of nano-iron oxide and 0.03g of sodium dodecyl sulfate, and continue stirring for 10 minutes to fully dissolve the sodium dodecyl sulfate, thus obtaining a mixed solution.
[0129] The mixed solution was placed in an ultrasonic cleaner and ultrasonically dispersed for 30 minutes at an ultrasonic power of 200W and a frequency of 40kHz to prepare a nano iron oxide suspension.
[0130] During ultrasonic dispersion, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0131] Step 4. Ionic liquid filling: The pretreated PTFE hollow fiber membrane was immersed in 45g of 1-butyl-3-methylimidazolium hexafluorophosphate using a vacuum-pressure impregnation method. The vacuum pump was started to reduce the pressure in the impregnation container to near vacuum (-0.1MPa) for 30 minutes.
[0132] After the vacuum treatment is completed, the vacuum pump is turned off, and an inert gas (nitrogen) is introduced into the container. The pressure is gradually increased to 0.5 MPa and maintained for 1 hour to allow the ionic liquid to fill the container, thus obtaining the first modified PTFE hollow fiber membrane.
[0133] Step 5. Preparation of PDA coating: Remove the initially modified PTFE hollow fiber membrane and blot the surface of the ionic liquid with filter paper.
[0134] The primary modified PTFE hollow fiber membrane was immersed in a dopamine hydrochloride solution and left to stand at room temperature for 12 hours to allow the dopamine hydrochloride to self-polymerize on the membrane surface to form a PDA coating, thus obtaining a secondary modified PTFE hollow fiber membrane.
[0135] During the soaking process, cover the mouth of the beaker with plastic wrap to reduce the oxidation of dopamine hydrochloride.
[0136] Step 6. Loading of nano-iron oxide: Remove the secondary modified PTFE hollow fiber membrane and rinse it with deionized water to remove unreacted dopamine hydrochloride.
[0137] The rinsed secondary modified PTFE hollow fiber membrane was immersed in a nano iron oxide suspension and placed in an ultrasonic cleaner for 30 minutes of ultrasonic treatment at a power of 100W and a frequency of 40kHz, so that the nano iron oxide was loaded onto the PDA coating, thus tertiary modified PTFE hollow fiber membrane.
[0138] During the ultrasonic treatment, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0139] Step 7. Drying: The modified PTFE hollow fiber membrane was removed three times and rinsed with deionized water to remove unloaded nano-iron oxide.
[0140] The tertiary modified PTFE hollow fiber membrane was placed in a vacuum drying oven and dried under vacuum at 40°C for 24 hours with a vacuum degree of 0.08 MPa to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
[0141] Test results: 1. Heavy metal ion adsorption performance test: Pb 2+ The adsorption capacity is 35 mg / g.
[0142] 2. Selective adsorption performance testing: Pb 2+ The adsorption capacity is 30 mg / g, Cd 2+ The adsorption capacity is 4 mg / g.
[0143] 3. Flux: The pure water flux is 315 L / (m²). 2 ·h).
[0144] 4. Acid and alkali resistance: Pure water flux is 245 L / (m³). 2 ·h).
[0145] Comparative Example 3 A method for preparing a PTFE hollow fiber membrane for treating heavy metal ions, which differs from Example 1 in that it includes the following steps: Step 1. Pretreatment of the PTFE hollow fiber membrane to be treated: 100g of the PTFE hollow fiber membrane to be treated was immersed in 95% ethanol solution and placed in an ultrasonic cleaner for ultrasonic cleaning for 30 minutes at an ultrasonic power of 200W and a frequency of 40kHz.
[0146] Remove the PTFE hollow fiber membrane to be treated and rinse it with plenty of deionized water until the pH of the effluent is 7, in order to remove the ethanol remaining on the membrane surface.
[0147] The cleaned PTFE hollow fiber membrane to be treated was placed in a vacuum drying oven and vacuum dried at 40°C for 12 hours with a vacuum degree of 0.08 MPa to obtain a pretreated PTFE hollow fiber membrane for later use.
[0148] Step 2. Preparation of dopamine hydrochloride solution: Add 500 mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at 300 rpm.
[0149] Add 1g of dopamine hydrochloride and 0.4g of tris(hydroxymethyl)aminomethane in sequence, and continue stirring until completely dissolved to obtain dopamine hydrochloride.
[0150] Measure the pH of the dopamine hydrochloride solution with a pH meter to ensure the pH is at 8.5. If the pH deviates from this value, adjust it to the target pH using hydrochloric acid or sodium hydroxide solution.
[0151] Step 3. Preparation of nano-iron oxide suspension: Add 500 mL of deionized water to a beaker, place it on a magnetic stirrer, and stir at 300 rpm.
[0152] Add 0.3g of nano-iron oxide and 0.03g of sodium dodecyl sulfate, and continue stirring for 10 minutes to fully dissolve the sodium dodecyl sulfate, thus obtaining a mixed solution.
[0153] The mixed solution was placed in an ultrasonic cleaner and ultrasonically dispersed for 30 minutes at an ultrasonic power of 200W and a frequency of 40kHz to prepare a nano iron oxide suspension.
[0154] During ultrasonic dispersion, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0155] Step 4. Preparation of PDA coating: The pretreated PTFE hollow fiber membrane was immersed in a dopamine hydrochloride solution and left to stand at room temperature for 12 hours to allow the dopamine hydrochloride to self-polymerize on the membrane surface to form a PDA coating, thus obtaining the first modified PTFE hollow fiber membrane.
[0156] During the soaking process, cover the mouth of the beaker with plastic wrap to reduce the oxidation of dopamine hydrochloride.
[0157] Step 5. Ionic liquid filling: Remove the initially modified PTFE hollow fiber membrane and rinse it with deionized water to remove unreacted dopamine hydrochloride.
[0158] The vacuum-pressure impregnation method was used to immerse the initially modified PTFE hollow fiber membrane in 45g of 1-butyl-3-methylimidazolium hexafluorophosphate. The vacuum pump was started to reduce the air pressure in the impregnation container to near vacuum (-0.1MPa) for 30 minutes.
[0159] After the vacuum treatment is completed, the vacuum pump is turned off, and an inert gas (nitrogen) is introduced into the container. The pressure is gradually increased to 0.5 MPa and maintained for 1 hour to allow the ionic liquid to fill the container, thus obtaining a secondary modified PTFE hollow fiber membrane.
[0160] Step 6. Loading of nano-iron oxide: Remove the secondary modified PTFE hollow fiber membrane and blot the surface of the ionic liquid with filter paper.
[0161] The rinsed secondary modified PTFE hollow fiber membrane was immersed in a nano iron oxide suspension and placed in an ultrasonic cleaner for 30 minutes of ultrasonic treatment at a power of 100W and a frequency of 40kHz, so that the nano iron oxide was loaded onto the PDA coating to obtain a tertiary modified PTFE hollow fiber membrane.
[0162] During the ultrasonic treatment, the temperature of the suspension is maintained below 30°C using an ice-water bath to prevent the agglomeration of nano-iron oxide.
[0163] Step 7. Drying: The modified PTFE hollow fiber membrane was removed three times and rinsed with deionized water to remove unloaded nano-iron oxide.
[0164] The tertiary modified PTFE hollow fiber membrane was placed in a vacuum drying oven and dried under vacuum at 40°C for 24 hours with a vacuum degree of 0.08 MPa to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
[0165] Test results: 1. Heavy metal ion adsorption performance test: Pb 2+The adsorption capacity is 38 mg / g.
[0166] 2. Selective adsorption performance testing: Pb 2+ The adsorption capacity is 35 mg / g, Cd 2+ The adsorption capacity is 4 mg / g.
[0167] 3. Flux: The pure water flux is 320 L / (m²). 2 ·h).
[0168] 4. Acid and alkali resistance: Pure water flux is 260L / (m³). 2 ·h).
[0169] Comparative Example 4 The PTFE hollow fiber membrane to be treated prepared in Example 1 is used as Comparative Example 4.
[0170] Test results: 1. Heavy metal ion adsorption performance test: Pb 2+ The adsorption capacity is 4 mg / g.
[0171] 2. Selective adsorption performance testing: Pb 2+ The adsorption capacity was 3.5 mg / g, Cd 2+ The adsorption capacity is 0.8 mg / g.
[0172] 3. Flux: The pure water flux is 140 L / (m²). 2 ·h).
[0173] 4. Acid and alkali resistance: Pure water flux is 136 L / (m³). 2 ·h).
[0174] The comparison of the detection data of Comparative Example 4 and Example 1 shows that Example 1 has a significant treatment effect on heavy metals, while maintaining high throughput and high acid and alkali resistance.
[0175] Comparative Examples 1-3 differed from Example 1 by altering a specific order. A comparison of the test data between Comparative Examples 1-3 and Example 1 shows that the performance of Comparative Examples 1-3 in terms of heavy metal treatment efficiency, flux, and acid / alkali resistance is significantly inferior to that of Example 1. This indicates that changing the preparation order prevents the acquisition of the desired complex structure, thus hindering the achievement of the expected performance of the hollow fiber membrane.
[0176] It should be understood that the application of this application is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of this application.
Claims
1. A method for preparing a PTFE hollow fiber membrane for treating heavy metal ions, characterized in that, Includes the following steps: A dopamine hydrochloride solution was prepared using water, dopamine hydrochloride, and tris(hydroxymethyl)aminomethane, with a pH of 8.5 ± 0.
2. A nano-iron oxide suspension was prepared by ultrasonic mixing of water, nano-iron oxide, and sodium dodecyl sulfate. The PTFE hollow fiber membrane to be treated is immersed in dopamine hydrochloride solution and reacted for 12-24 hours to obtain the primary modified PTFE hollow fiber membrane. The primary modified PTFE hollow fiber membrane was immersed in a nano iron oxide suspension and ultrasonically treated to obtain the secondary modified PTFE hollow fiber membrane. A secondary modified PTFE hollow fiber membrane was immersed in 1-butyl-3-methylimidazolium hexafluorophosphate using a vacuum-pressure impregnation method to obtain a tertiary modified PTFE hollow fiber membrane. The PTFE hollow fiber membrane, modified three times, is dried to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
2. The method for preparing a PTFE hollow fiber membrane for treating heavy metal ions according to claim 1, characterized in that, When the modified PTFE hollow fiber membrane is first immersed in the nano iron oxide suspension, the ultrasonic treatment conditions are: 20-60 minutes, ultrasonic power of 50-150W, and frequency of 35-45kHz.
3. The method for preparing a PTFE hollow fiber membrane for treating heavy metal ions according to claim 1, characterized in that, Vacuum-pressure impregnation methods include: The modified PTFE hollow fiber membrane was immersed in 1-butyl-3-methylimidazolium hexafluorophosphate, and the air pressure in the immersion container was reduced to near vacuum for 20-60 minutes. After vacuum treatment, inert gas is introduced and the pressure is gradually increased to 0.5MPa±0.05, and maintained for 1-2 hours to obtain a tertiary modified PTFE hollow fiber membrane.
4. The method for preparing a PTFE hollow fiber membrane for treating heavy metal ions according to claim 1, characterized in that, The preparation of the nano iron oxide suspension includes: adding nano iron oxide and sodium dodecyl sulfate to water, stirring at 250-350 rpm for 5-20 minutes to obtain a mixed solution; The mixed solution was dispersed for 20-60 minutes under ultrasonic power of 100-300W and frequency of 35-45kHz to obtain a nano iron oxide suspension.
5. The method for preparing a PTFE hollow fiber membrane for treating heavy metal ions according to claim 1, characterized in that, The drying of tertiary modified PTFE hollow fiber membrane includes: descaling of tertiary modified PTFE hollow fiber membrane; Then, it is vacuum dried at 35-45℃ for 24-48 hours with a vacuum degree of 0.08MPa±0.005 to obtain a PTFE hollow fiber membrane for treating heavy metal ions.
6. The method for preparing a PTFE hollow fiber membrane for treating heavy metal ions according to claim 1, characterized in that, After pretreatment, the PTFE hollow fiber membrane to be treated is then immersed in dopamine hydrochloride solution; The pretreatment of the PTFE hollow fiber membrane to be treated includes: The PTFE hollow fiber membrane to be treated was ultrasonically cleaned using an ethanol solution. Remove the PTFE hollow fiber membrane to be treated, rinse it with water until the pH of the effluent is 6.5-7.5, and then vacuum dry it at 35-45℃ for 12-24 hours with a vacuum degree of 0.08±0.02MPa to obtain the pretreated PTFE hollow fiber membrane.
7. The method for preparing a PTFE hollow fiber membrane for treating heavy metal ions according to claim 6, characterized in that, Ultrasonic cleaning of the PTFE hollow fiber membrane to be treated using ethanol solution includes immersing the PTFE hollow fiber membrane to be treated in ethanol solution and ultrasonically cleaning for 20-60 minutes under ultrasonic power of 100-300W and frequency of 35-45kHz.
8. The method for preparing a PTFE hollow fiber membrane for treating heavy metal ions according to claim 1, characterized in that, The preparation of the PTFE hollow fiber membrane to be treated includes: PTFE resin and additive oil are mixed, and then preformed and extruded to obtain nascent PTFE hollow fibers. Heat-treated nascent PTFE hollow fibers were subjected to heat treatment at 300℃-350℃ for 60min-150min to obtain heat-treated PTFE hollow fibers. Heat-treated PTFE hollow fibers are stretched to obtain stretched PTFE hollow fibers. The stretching conditions are: stretching temperature 30℃-330℃, stretching ratio 0.5-10 times, and stretching speed 0.3m / min-35m / min. Sintering and stretching PTFE hollow fibers at 330℃-370℃ for 5min-20min; After sintering, the stretched PTFE hollow fibers are cooled to obtain the PTFE hollow fiber membrane to be processed.
9. A PTFE hollow fiber membrane for treating heavy metal ions prepared by the method for preparing a PTFE hollow fiber membrane for treating heavy metal ions according to any one of claims 1-8.
10. The PTFE hollow fiber membrane for treating heavy metal ions according to claim 9, characterized in that, The preparation materials include: 95-105 parts by weight of PTFE hollow fiber membrane to be treated, 0.1-1 parts by weight of dopamine hydrochloride, 0.1-1 parts by weight of tris(hydroxymethyl)aminomethane, 0.1-1 parts by weight of nano-iron oxide, 0.01-0.1 parts by weight of sodium dodecyl sulfate, 38-48 parts by weight of 1-butyl-3-methylimidazolium hexafluorophosphate, and 800-1500 parts by weight of water.
Citation Information
Patent Citations
Preparation method and application of dual self-cleaning polytetrafluoroethylene microporous membrane
CN120094428A
Ionic liquid-solid-polymer mixed matrix membranes for gas separations
US7943543B1
